Olahan Ikan Air Tawar Aneka Rasa - Nurfaizah AP; Haerani Haerani; Hotimah Hotimah (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
This PKM aims to improve the skills of housewives in creating various flavors of fresh water fish, and creating self-reliance in entrepreneurship. The benefits obtained from the implementation of the activity are (1) Gaining knowledge and skills about processed freshwater fish of various flavors, (2) Gaining knowledge about entrepreneurship. This activity was held on Saturday and Sunday 19-20 June 2021 with 10 participants. The implementation method is through the stages of potential identification, needs analysis, work plan, training, monitoring and evaluation. The training method used is Lecture, Discussion, Demonstration, Practice, and Observation. PKM activities can be carried out according to planning because: 1) Good cooperation between the implementing team and local village officials, 2) Participation of all training participants. 3) Potential strategic location to develop production, 4) Availability of raw materials for product development 5) Strategic place of business strongly supports the expansion of marketing network. The conclusion is that the results of the implementation of PKM activities are in the very good category. This can be seen from the aspect of the suitability of the program with the needs of partners, indicating that there is conformity. Aspects of program implementation to achieve successful activities well. The aspect of delivering training materials for housewives reached the very good category, and the mentoring aspect was in the good category. Suggestions need to be more intensive socialization about products produced from processed freshwater fish of various flavors so that people know products made from local raw materials through online promotions on Instagram or WhatsApp.